Anode material of solid oxide electrolytic cell as well as preparation method and application of anode material

By screen printing of LSM and LSCF composite materials on the electrolyte layer of the solid oxide electrolytic cell, an anode material with a laminated structure is solved, and the life of the electrolytic cell is improved.

CN119542434APending Publication Date: 2025-02-28NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411461936.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The electrochemical reaction uniformity of existing solid oxide electrolytic cells leads to uneven current density distribution, uneven temperature distribution, local stress distribution, and reduced electrolytic cell life.

Method used

Using an anode material including LSM and LSCF composite materials, two materials are printed on the electrolyte layer by screen printing technology and sintered to form an anode material with a laminated structure.

Benefits of technology

It improves the uniformity and activity of electrochemical reactions, reduces local stress concentration, improves the current density distribution, and thus extends the life of the electrolytic cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542434A_ABST
    Figure CN119542434A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fuel cells, and provides an anode material of a solid oxide electrolytic cell (SOEC) as well as a preparation method and application of the anode material. The preparation method comprises the following steps: preparing first slurry and second slurry; if the SOEC is rectangular, first slurry is printed at the 1 / 3 position, close to the fuel gas inlet, of the electrolyte layer, and second slurry is printed at the remaining 2 / 3 position of the electrolyte layer; if the SOEC is square, printing a first sizing agent at the central position of the electrolyte layer, and printing a second sizing agent at the position outside the center; and sintering the printed electrolyte layer. The invention also discloses an anode material of the SOEC prepared according to the method, and the SOEC which comprises the anode material, an electrolyte layer, a barrier layer and a cathode material. The anode material disclosed by the invention comprises two materials, so that the phenomena of higher local temperature and higher reaction degree of the electrolytic tank can be improved, the reaction uniformity is improved, the local stress concentration is reduced, and the current density distribution is improved, thereby prolonging the service life of the electrolytic tank.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of fuel cell technology, and in particular to an anode material of a solid oxide electrolytic cell and a preparation method and application thereof. Background Art

[0002] The larger the active area of ​​the electrode of the solid oxide electrolytic cell (SOEC), the lower the uniformity of the electrochemical reaction, resulting in uneven current density distribution, uneven temperature distribution, and thus excessive local stress distribution, resulting in electrolytic cell failure. Some current technologies mainly focus on improving the overall activity of the electrochemical reaction, but do not improve the uniformity of the electrochemical reaction, that is, they cannot solve the problem of uniformity of current density distribution in the electrolytic cell.

[0003] Based on this, it is of great significance to provide a method for improving the uniformity of electrochemical reactions in solid oxide electrolytic cells. Summary of the invention

[0004] The present disclosure provides an anode material for a solid oxide electrolytic cell and a preparation method and application thereof, so as to at least solve the above technical problems existing in the prior art.

[0005] According to a first aspect of the present disclosure, there is provided a method for preparing an anode material for a solid oxide electrolytic cell (SOEC), comprising the following steps:

[0006] S1: mixing the LSM composite material with terpineol, ethyl cellulose and a dispersant to obtain a first slurry;

[0007] S2: mixing the LSCF composite material with pinene alcohol, ethyl cellulose and a dispersant to obtain a second slurry;

[0008] S3: If the solid oxide electrolytic cell is rectangular, screen-print the first slurry at 1 / 3 of the electrolyte layer close to the fuel gas inlet, and screen-print the second slurry at the remaining 2 / 3 of the electrolyte layer;

[0009] If the solid oxide electrolytic cell is square, the first slurry is screen-printed at the center of the electrolyte layer, and the second slurry is screen-printed at a position outside the center of the electrolyte layer;

[0010] S4: Sintering the electrolyte layer after screen printing in step S3 to obtain the anode material of the solid oxide electrolytic cell.

[0011] In one embodiment, the solid oxide electrolytic cell has a flat plate structure.

[0012] Specifically, the solid oxide electrolytic cell includes an anode material, an electrolyte layer, a barrier layer, and a cathode material (support material layer). In the above method, the first slurry and the second slurry are printed on the electrolyte layer to prepare the anode material of the solid oxide electrolytic cell.

[0013] In one embodiment, the method for preparing the LSM composite material in step S1 comprises the following steps: 1- x Sr x MnO 3 (LSM, 0≤x≤0.5) is mixed with a carbon material to prepare an LSM / carbon material composite material; and the LSM / carbon material composite material is mixed with an electrolyte material to obtain the LSM composite material.

[0014] Specifically, the La 1-x Sr x MnO 3 The particle diameter of (0≤x≤5) is 0.4~1μm.

[0015] Specifically, the carbon material is selected from at least one of graphite, carbon nanotubes and graphene.

[0016] More specifically, the carbon material is selected from graphite, and the particle diameter of the graphite is less than 1 μm.

[0017] Specifically, in the LSM / carbon material composite material, the volume fraction of the carbon material is 15-30%.

[0018] More specifically, in the LSM / carbon material composite material, the volume fraction of the carbon material is 20%.

[0019] Specifically, the particle size of the LSM / carbon material composite material is 20 to 60 μm.

[0020] Specifically, the electrolyte material is selected from any one of ScSZ, SDC, and GDC.

[0021] ScSZ is cerium oxide (CeO 2 ) doped with scandium oxide (Sc 2 O 3 ) Stabilized Zirconia (ZrO 2 ), preferably (Sc 2 O 3 ) 0.1 (CeO 2 ) 0.01 (ZrO 2 ) 0.89 ; SDC is Sm x Ce 1-x O 2(0≤x≤0.5), preferably Ce 0.8 Sm 0.2 O 2 ; GDC is Gd x Ce 1-x O 2 (0≤x≤0.5).

[0022] Specifically, the mass ratio of the LSM / carbon material composite material to the electrolyte material is 1 to 5:1.

[0023] In one embodiment, in step S1, the mass ratio of the LSM composite material to the terpineol, the ethyl cellulose and the dispersant is 20:5:1:2.

[0024] In one embodiment, the dispersant is selected from at least one of triethanolamine, citric acid, polyethylene glycol, acetylacetone, polyvinyl pyrrolidone, and polyacrylic acid.

[0025] In one embodiment, step S1 mixes the LSM composite material with the pine alcohol, the ethyl cellulose and the dispersant by ball milling, the ball milling time is 1 to 12 hours, and the ratio of the mass of the ball milling beads to the total mass of the LSM composite material, the pine alcohol, the ethyl cellulose and the dispersant is 1:1 to 2.

[0026] Specifically, the ball milling beads are zirconium oxide ball milling beads with a particle size of 3 to 20 mm.

[0027] For example, the particle size of the ball milling beads is selected to be 3 mm, 5 mm or 10 mm, and the ratio of the mass of the ball milling beads to the total mass of the LSM composite material, pinene alcohol, ethyl cellulose and dispersant is 1:2.

[0028] In one embodiment, the method for preparing the LSCF composite material in step S2 comprises the following steps: 1- x Sr x Co 1-y Fe y O 3 (0≤x≤1, 0≤y≤1) is mixed with a carbon material to prepare a LSCF / carbon material composite material; and the LSCF / carbon material composite material is mixed with an electrolyte material to obtain the LSCF composite material.

[0029] Specifically, the specific details of the above method for preparing the LSCF composite material are the same as the details of the method for preparing the LSM composite material in step S1, and will not be repeated here.

[0030] Specifically, the mass ratio of the LSCF / carbon material composite material to the electrolyte material is 1 to 5:1.

[0031] In one possible implementation, step S3 uses a 60-100 mesh screen to perform the screen printing.

[0032] Specifically, the pattern of the screen printing is not specifically limited. For example, the printing pattern of the first slurry can be rectangular, circular or square, and the remaining part is the printing pattern of the second slurry.

[0033] In one possible implementation manner, the thickness of the first slurry and the second slurry screen-printed in step S3 is 10-30 μm.

[0034] In one embodiment, the sintering temperature in step S4 is 1000-1200° C. and the sintering time is 100-150 min.

[0035] According to a second aspect of the present disclosure, an anode material for a solid oxide electrolytic cell prepared according to the above preparation method is provided.

[0036] According to a third aspect of the present disclosure, a solid oxide electrolytic cell is provided, comprising the above-mentioned anode material, a barrier layer, an electrolyte layer and a cathode material arranged in a stacked manner.

[0037] In one embodiment, the material of the electrolyte layer is YSZ.

[0038] In one embodiment, the material of the barrier layer is selected from at least one of SDC, ScSZ, and GDC.

[0039] In one possible implementation manner, the cathode material is a mixture of NiO and YSZ, wherein the mass fraction of NiO is 20-80%.

[0040] According to an implementable embodiment of the present disclosure, at least the following beneficial effects are achieved:

[0041] For existing solid oxide electrolytic cells, the anode material generally only includes one kind, which will result in that during the electrochemical reaction, some places on the surface of the electrolytic cell react quickly and some places react slowly, and the reaction and temperature of the entire electrolytic cell are uneven, which further leads to uneven distribution of current density, and thus uneven distribution of local stress, and reduces the life of the electrolytic cell. The anode material prepared by the present disclosure includes two different materials, and by sintering different shapes on the surface of the electrolyte layer, it can effectively improve the phenomenon of high local temperature and high reaction degree of the electrolytic cell, improve the uniformity and activity of the overall electrochemical reaction, reduce local stress concentration, and improve the current density distribution, thereby increasing the life of the electrolytic cell.

[0042] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, in which:

[0044] In the drawings, the same or corresponding reference numerals represent the same or corresponding parts.

[0045] Figure 1 A schematic diagram of a screen printing pattern when preparing an anode material in Example 1 of the present disclosure is shown;

[0046] Figure 2 A schematic diagram of a screen printing pattern when preparing an anode material in Example 2 of the present disclosure is shown;

[0047] Figure 3 A schematic diagram of a screen printing pattern when preparing an anode material in Example 3 of the present disclosure is shown;

[0048] Figure 4 A schematic diagram of a screen printing pattern for preparing anode material in Example 4 of the present disclosure is shown;

[0049] Figure 5 A schematic diagram of a screen printing pattern when preparing an anode material in Example 5 of the present disclosure is shown;

[0050] Figure 6 The temperature distribution test diagrams at different current densities at three positions of the fuel gas inlet, middle and outlet of the anode materials of Example 1 and Comparative Example 1 in the test examples of the present disclosure are shown. DETAILED DESCRIPTION

[0051] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0052] Example 1

[0053] In this embodiment, an anode material 1 for a solid oxide electrolytic cell is prepared, and the specific process is as follows:

[0054] (1) La0.8 Sr 0.2 MnO 3 The LSM / graphite composite material with a particle size of 20 to 60 μm was prepared by agglomeration of (LSM) micropowder (particle diameter of 0.4 to 1 μm) and graphite micropowder with a particle diameter of less than 1 μm, wherein the volume fraction of graphite micropowder was 20%. 0.2 Ce 0.8 O 2 (GDC), the mass ratio of LSM / graphite composite material to GDC is 4:1, and LSM composite material is obtained. The LSM composite material is evenly mixed with pineneol, ethyl cellulose and dispersant triethanolamine in a mass ratio of 20:5:1:2 by ball milling to obtain the first slurry; wherein, zirconium oxide ball milling beads (particle size of 5mm) are selected for ball milling, the mass ratio of the ball milling beads to the total mass of the LSM composite material, pineneol, ethyl cellulose and dispersant is 1:2, and the ball milling time is 10h.

[0055] (2) La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3 LSCF and graphite powder with a particle diameter of less than 1 μm were agglomerated to prepare LSCF / graphite composite materials with a particle size of 20 to 60 μm, wherein the volume fraction of graphite powder was 20%. 0.2 Ce 0.8 O 2 (GDC), the mass ratio of LSCF / graphite composite material to GDC is 4:1, and LSCF composite material is obtained. The LSCF composite material is evenly mixed with pine alcohol, ethyl cellulose and dispersant triethanolamine in a mass ratio of 20:5:1:2 by ball milling to obtain the second slurry; wherein, zirconium oxide ball milling beads (particle size of 5mm) are selected for ball milling, the mass ratio of the ball milling beads to the total mass of the LSM composite material, pine alcohol, ethyl cellulose and dispersant is 1:2, and the ball milling time is 10h.

[0056] (3) The solid oxide electrolytic cell in this embodiment is a rectangular electrolytic cell with a length × width of 230 × 150 mm. The first slurry is screen-printed at 1 / 3 of the electrolyte layer near the fuel gas inlet, and the second slurry is screen-printed at the remaining 2 / 3 of the electrolyte layer. The thickness of the first slurry and the second slurry is 20 μm. Screen printing is performed using an 80-mesh screen; the screen printing pattern is as follows: Figure 1 As shown, the electrolytic cell is rectangular as a whole, two short sides are arc-shaped, and the junction of the printed first slurry and the second slurry is an arc line.

[0057] (4) The screen-printed electrolyte layer of step (3) is calcined in air at 1050° C. for 120 min to obtain an anode material 1 for a solid oxide electrolytic cell.

[0058] Example 2

[0059] In this embodiment, anode material 2 of a solid oxide electrolytic cell is prepared. The specific process is the same as that of embodiment 1, except that the pattern of screen printing in step (3) of this embodiment is different from that of embodiment 1.

[0060] The pattern of screen printing in this embodiment is as follows Figure 2 As shown, the electrolytic cell is rectangular as a whole, and the junction of the printed first slurry and the second slurry is a straight line.

[0061] Example 3

[0062] In this embodiment, anode material 3 of a solid oxide electrolytic cell is prepared. The specific process is the same as that in embodiment 1, except that the pattern of screen printing in step (3) of this embodiment is different from that of embodiment 1.

[0063] The pattern of screen printing in this embodiment is as follows Figure 3 As shown, the electrolytic cell is rectangular as a whole, and the junction of the printed first slurry and the second slurry is an arc.

[0064] Example 4

[0065] In this embodiment, anode material 4 of a solid oxide electrolytic cell is prepared. The specific process is the same as that of embodiment 1, except that the pattern of screen printing in step (3) of this embodiment is different from that of embodiment 1.

[0066] The solid oxide electrolytic cell in this embodiment is a square electrolytic cell with a length×width of 150×150 mm. The first slurry is screen-printed at the center of the electrolyte layer, and the second slurry is screen-printed at a position outside the center of the electrolyte layer. The thickness of the first slurry and the second slurry is 20 μm. The screen printing is performed using an 80-mesh screen; the screen printing pattern is as follows: Figure 4 As shown, the electrolytic cell is square as a whole, the center position where the first slurry is printed is circular, and the remaining part is printed with the second slurry.

[0067] Example 5

[0068] In this embodiment, anode material 5 of a solid oxide electrolytic cell is prepared. The specific process is the same as that of embodiment 1, except that the pattern of screen printing in step (3) of this embodiment is different from that of embodiment 1.

[0069] The solid oxide electrolytic cell in this embodiment is a square electrolytic cell with a length×width of 150×150 mm. The first slurry is screen-printed at the center of the electrolyte layer, and the second slurry is screen-printed at a position outside the center of the electrolyte layer. The thickness of the first slurry and the second slurry is 20 μm. The screen printing is performed using an 80-mesh screen; the screen printing pattern is as follows: Figure 5 As shown, the electrolytic cell is a square as a whole, the center position where the first slurry is printed is a square, and the remaining part is printed with the second slurry.

[0070] Example 6

[0071] In this embodiment, a solid oxide electrolytic cell LSM-GDC / GDC / YSZ / NiO-YSZ is prepared, which specifically includes anode material 1 (LSM-GDC) prepared in Example 1, a barrier layer, an electrolyte layer and a cathode material arranged in a stacked manner. The material of the electrolyte layer is YSZ; the material of the barrier layer is GDC, and the cathode material is a mixture of NiO and YSZ.

[0072] Comparative Example 1

[0073] This comparative example provides a single anode material LSCF for a solid oxide electrolytic cell.

[0074] Test example

[0075] The temperature distribution of the fuel gas inlet, middle and outlet of the anode materials of Example 1 and Comparative Example 1 at different current densities was tested. The results are as follows: Figure 6 shown. Figure 6 It is shown that the temperature changes at the fuel gas inlet and the middle of the anode material of Comparative Example 1 at different current densities are significantly different, while the temperatures of the fuel gas inlet, middle and outlet of the anode material of Example 1 at different current densities are relatively constant, further proving that the anode material prepared by the method of the present invention can effectively improve the phenomenon of high local temperature and high reaction degree in the electrolytic cell, improve the uniformity of the overall electrochemical reaction, reduce local stress concentration, and thus increase the life of the electrolytic cell.

[0076] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solution of this disclosure can be achieved, and this document is not limited here.

[0077] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present disclosure, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0078] The above is only a specific embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A method for preparing an anode material for a solid oxide electrolytic cell, characterized in that: The following steps are involved: S1: mixing the LSM composite material with terpineol, ethyl cellulose and a dispersant to obtain a first slurry; S2: mixing the LSCF composite material with pinene alcohol, ethyl cellulose and a dispersant to obtain a second slurry; S3: If the solid oxide electrolytic cell is rectangular, screen-print the first slurry at 1 / 3 of the electrolyte layer close to the fuel gas inlet, and screen-print the second slurry at the remaining 2 / 3 of the electrolyte layer; If the solid oxide electrolytic cell is square, the first slurry is screen-printed at the center of the electrolyte layer, and the second slurry is screen-printed at a position outside the center of the electrolyte layer; S4: Sintering the electrolyte layer after screen printing in step S3 to obtain the anode material of the solid oxide electrolytic cell.

2. The preparation method according to claim 1, characterized in that: Step S1 The method for preparing the LSM composite material comprises the following steps: 1-x Sr x MnO3 (0≤x≤0.5) is mixed with carbon material to prepare LSM / carbon material composite material; and the LSM / carbon material composite material is mixed with electrolyte material to obtain the LSM composite material.

3. The preparation method according to claim 2, characterized in that: The carbon material is selected from at least one of graphite, carbon nanotubes, and graphene; Preferably, in the LSM / carbon material composite material, the volume fraction of the carbon material is 15-30%; Preferably, the particle size of the LSM / carbon material composite material is 20-60 μm.

4. The preparation method according to claim 2, characterized in that: The electrolyte material is selected from any one of ScSZ, SDC, and GDC; Preferably, the mass ratio of the LSM / carbon material composite material to the electrolyte material is 1 to 5:

1.

5. The preparation method according to claim 1, characterized in that: Step S1: the mass ratio of the LSM composite material to the terpineol, the ethyl cellulose and the dispersant is 20:5:1:2; Preferably, the dispersant is selected from at least one of triethanolamine, citric acid, polyethylene glycol, acetylacetone, polyvinyl pyrrolidone, and polyacrylic acid; Preferably, in step S1, the LSM composite material is mixed with the terpineol, the vinyl cellulose and the dispersant by ball milling, the ball milling time is 1 to 12 hours, and the ratio of the mass of the ball milling beads to the total mass of the LSM composite material, the terpineol, the vinyl cellulose and the dispersant is 1:1 to 2.

6. The preparation method according to claim 1, characterized in that: Step S2 The method for preparing the LSCF composite material comprises the following steps: 1-x Sr x Co 1-y Fe y O3 (0≤x≤1, 0≤y≤1) is mixed with a carbon material to prepare a LSCF / carbon material composite material; the LSCF / carbon material composite material is mixed with an electrolyte material to obtain the LSCF composite material; Preferably, the mass ratio of the LSCF / carbon material composite material to the electrolyte material is 1 to 5:

1.

7. The preparation method according to claim 1, characterized in that: Step S3: using a 60-100 mesh screen to perform the screen printing; Preferably, the thickness of the first slurry and the second slurry screen-printed in step S3 is 10-30 μm; Preferably, the sintering temperature in step S4 is 1000-1200° C. and the sintering time is 100-150 min.

8. An anode material for a solid oxide electrolytic cell obtained according to the preparation method according to any one of claims 1 to 7.

9. A solid oxide electrolytic cell, characterized in that: The solid oxide electrolytic cell comprises the anode material according to claim 8, a barrier layer, an electrolyte layer and a cathode material which are stacked.

10. The solid oxide electrolytic cell according to claim 9, characterized in that: The material of the electrolyte layer is YSZ; Preferably, the material of the barrier layer is selected from at least one of SDC, ScSZ and GDC; Preferably, the cathode material is a mixture of NiO and YSZ, wherein the mass fraction of NiO is 20-80%.

Citation Information

Cited By

  • Two-phase composite material powder, method for preparing two-phase composite material powder based on cooperation of sol-gel method and spray drying and application of two-phase composite material powder

    CN120903575A